EMPOWERING ISLAMIC COMMUNITIES IN OPTIMIZING THE ROLE OF BHABINKAMTIBMAS THROUGH COMMUNITY-BASED MOVEMENTS IN CENTRAL LAMPUNG - Rafika, Ridho; Romli, Khomsahrial; Yanti, Fitri; Fauzi, Fauzi; Setiawati, Rini (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Community security and order is a situation that is needed to support the implementation of development and all community activities. Babinkamtibmas received an award from the Bangun Rejo Polsek for being active in community activities, not easily influenced, guaranteed and having good security and order. This research method is descriptive qualitative. The data needed are primary and secondary. Then the way to collect data in this study is by observation, interviews and documentation. The study results a show that the Islamic community empowerment model in optimizing the role of Babinkamtibmas through community-based movements in Bangun Rejo District, Central Lampung Regency, is as follows 1) The Coaching and Assistance Model is to guide the community about awareness so that they have a high social spirit. 2) The Partnership Model prioritizes approaches to the community, such as establishing friendly relations with village/village officials, religious leaders, community leaders and others. 3) The service model is conducting visits to the village head, village officials and the community, disseminating information regarding maintaining security and public order. Of the three models, the authors found the ideal model, namely the Humanist-Dynamic model, which can also be called the Community Based Humanist Dynamic model